Effects of vegetation restoration on soil aggregate characteristics and soil erodibility at gully head in Loess hilly and gully region - Ji Wu; Guang Yang; Yunxia Ma; Xinyu Guo; Naijing Lu; Zeqing Chen; Zimeng Wang; Ning Wang; Hai Du (Scientific Reports)
Abstract Vegetation restoration can be effective in containing gully head advance. However, the effect of vegetation restoration type on soil aggregate stability and erosion resistance at the head of the gully is unclear. In this study, five types of vegetation restoration—Pinus tabulaeformis (PT), Prunus sibirica (PS), Caragana korshinskii (CKS), Hippophae rhamnoides (HR), and natural grassland (NG, the dominant species is Leymus chinensis)—in the gully head were studied. Soil aggregate composition and nutrient contents in the 0–20, 20–40, and 40–60 cm soil layers were also determined, and the soil stability parameters were used to evaluate the soil conditions. The soil erodibility (K) was then determined by measuring the granulometric composition and organic matter. The results showed that the particle size of soil aggregates under different vegetation restoration types was mainly < 0.25 mm, and the percentage of aggregate disruption (PAD) was 22.08–76.07%. This further indicated that in Loess hilly and gully regions, water-stable aggregates were more reflective of the stability of soil aggregates in a gully head under vegetation restoration. The > 0.25 mm aggregates (R> 0.25 mm), geometric mean diameter (GMD), and mean weight diameter (MWD) values of the three soil layers were the highest in PT and the lowest in NG, while the opposite was true for fractal dimension (D) and the percentage of aggregate disruption (PAD). The K ranged from 0.052 to 0.065 t·hm2·h·MJ− 1 mm− 1·hm− 2. GMD can be used to characterize the anti-erosion ability of soil, and increasing the soil organic carbon, total nitrogen, and clay content can effectively reduce soil erodibility. The comprehensive analysis indicated that the soil aggregates of arbors planted in the gully head had the highest stability and anti-erodibility, followed by shrubs and grasslands, and can be used to evaluate vegetation restoration measures in gully heads.